Cladistic analysis and osteological descriptions of the frog species in the Leptodactylus fuscus species group (Anura, Leptodactylidae) - Ponssa, María Laura (2008)
The genus Leptodactylus is predominantly Neotropical (a few species have colonized the southern Neartic region) and is distributed from Texas to Argentina and on certain Caribbean islands. Leptodactylus was divided into five groups of species: Leptodactylus melanonotus, Leptodactylus ocellatus, Leptodactylus fuscus, Leptodactylus pentadactylus and Leptodactylus marmoratus. Among these, the L. fuscus group is the one with most species, with 27 taxa. Characters unverified in most of the species are used to define the L. fuscus group. However, the monophyly of the group has never been tested rigorously in a quantitative phylogenetic context. Thus, the main goal of this study was to test such monophyly and to construct a phylogeny of the L. fuscus group. A matrix of 114 characters scored across 43 taxa was constructed, with 31 characters taken from external morphology, 58 from adult skeletons, 16 from larval chondrocranium, 5 from ethology and 4 from orphometric data were included. Out of all the species examined, 23 belonged to the ingroup and 20 to the outgroup. The data set was analysed with implied weights, by using TNT software. The monophyly of the group was strongly supported in the fittest cladogram obtained. The optimizations of some characters on this hypothesis support traditional evolutionary hypotheses. The optimizations also suggest the presence of paedomorphic character states in some species, which is also discussed.